Emphysematous pyelonephritis in patient with hemophagocytic lymphohistiocytosis: A case report (Indian Journal of Case Reports, 2024)
Emphysematous pyelonephritis (EPN) and hemophagocytic lymphohistiocytosis (HLH) are rare, fatal illnesses. The presence of both at once in a patient is extremely rare. The number of reported cases of EPN is <800 cases worldwide to date. Contrarily, the prevalence of adults with HLH is estimated to be 1 in every 2000 adults admitted to a tertiary health center. This case report aims to present the case of a 45-year-old woman who was diagnosed with EPN with a history of HLH and was successfully treated with medication alone. In conclusion, the clinical manifestations of EPN are non-specific and need imaging modalities like computed tomography (CT) scans. Treating EPN is based on CT scan classification. Medical treatment was an option for these patients. There is no direct association between EPN and HLH; it is a challenging decision to treat patients with both.